Compatible stem volume and taper equations for Cilicica fir - Onur Alkan; Ramazan Ozçelik (Turkish Journal of Forestry, 2021)
Four taper estimating systems were evaluated for Cilicica fir (Abies cilicica Carr.) in Turkey to demonstrate statistical and practical considerations that should be used when selecting a taper estimating system for forest inventory purposes. The four equations selected were: Kozak et al. (1969), Demaerschalk (1972), Max and Burkhart (1976), and Clark et al. (1991). Tested models have been compared using evaluation statistics like as: mean difference (MD), standard error of the estimate (SEE), and Fit index (FI). Clark et al. (1991)’s segmented taper model was superior in predicting Cilicica fir stem form and stem volume than the other models. However, since this model also requires the measurement of the upper stem diameter value at 5.30 m for stem diameter and volume estimations, it was concluded that Max and Burkhart (1976) model is more suitable for practical forestry purposes among the models tested. Clark et al.’s, Max and Burkhart’s, and Demaerschalk’s models showed consistent prediction performances for both the whole stem and different parts of the stem in terms of MD and SEE values in diameter and volume estimates. Average diameter and volume prediction errors were less than 2.0 cm and 0.01 m3, respectively. All models produced reliable results for diameter and merchantable taper volume estimates at any point, based on 10 different relative height classes.